2018
DOI: 10.1186/s12866-018-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

A metagenome-wide association study of gut microbiota in asthma in UK adults

Abstract: BackgroundAsthma, one of the most common chronic respiratory disorders, is associated with the hyper-activation of the T-cell subset of adaptive immunity. The gut microbiota may be involved in the development of asthma through the production of short-chain fatty acids (SCFAs), exhibiting modulatory effects on Th. So, we performed a metagenome-wide association study (MWAS) of the fecal microbiota from individuals with asthma and healthy controls. And that was the first case to resolve the relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 26 publications
5
95
1
Order By: Relevance
“…It is possible, however, that the difficulty encountered in reproducing not only inflammation but also airway obstruction and clinical signs with inhalation challenges are limited by the fact that they bypass the gastrointestinallung axis. 21,22 Finally, unlike a recent study that showed decreased diversity in adults with asthma, 23 we did not observe differences in diversity. Differences could arise from the fact that most asthmatic patients are on corticosteroids because medication is not typically withheld for such studies.…”
Section: Differences Between Healthy and Asthmatic Horsescontrasting
confidence: 94%
“…It is possible, however, that the difficulty encountered in reproducing not only inflammation but also airway obstruction and clinical signs with inhalation challenges are limited by the fact that they bypass the gastrointestinallung axis. 21,22 Finally, unlike a recent study that showed decreased diversity in adults with asthma, 23 we did not observe differences in diversity. Differences could arise from the fact that most asthmatic patients are on corticosteroids because medication is not typically withheld for such studies.…”
Section: Differences Between Healthy and Asthmatic Horsescontrasting
confidence: 94%
“…Recently, the distinct gut microbiota has also been revealed in adult asthmatics 26,27 . Supporting this phenomenon, microbe-derived short-chain fatty acids were suggested as possible mediators in the pathogenesis of asthma 28 . Our study demonstrated the alteration of overall body microbiota in established adult asthmatics by using blood EVs.…”
Section: Discussionmentioning
confidence: 92%
“…Gut microbiota composition is largely determined by exposure to dietary factors, but conversely, gut microbiota are needed for digestion of macronutrients and production of a wide range of metabolites [ 5 ]. Alterations in gut microbiota composition have been observed in a variety of health conditions, including type 2 diabetes, inflammatory bowel disease, asthma, psychiatric disorders, but also in cardiovascular disease [ 6 , 7 , 8 , 9 , 10 ]. In addition, several gut metabolites have been shown to interact with metabolism and the nervous system, affecting insulin sensitivity, energy balance, and appetite regulation [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%